WARDAH’S CUSTOMER SATISFACTION REGARDING PRODUCT PACKAGING INNOVATION, QUALITY AND PRICE: JAKARTA AREA - Putri, Theresia Wongso; Napitupulu, Elfrida Viesta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Many new brands of body and beauty care products have sprung up, we can find almost all varieties from local products and other products that came from other countries. With the fast development of these brands, Wardah needs to be able to take part in